Stability of Attachment Style in Adolescence: An Empirical Test of Alternative Developmental Processes. Issue 3 (16th March 2017) - Jones, Jason D.; Fraley, R. Chris; Ehrlich, Katherine B.; Stern, Jessica A.; Lejuez, C. W.; Shaver, Phillip R.; Cassidy, Jude
Abstract : Few studies have examined stability and change in attachment during adolescence. This 5‐year longitudinal study (a) examined whether prototype or revisionist developmental dynamics better characterized patterns of stability and change in adolescent attachment (at T1, N  =   176; M age  = 14.0 years, SD  = 0.9), (b) tested potential moderators of prototype‐like attachment stability, and (c) compared attachment stability in adolescence to stability in adulthood. The results supported the prototype model, which assumes that there is a stable, enduring factor underlying stability and change in attachment. Exploratory moderation analyses revealed that family conflict, parental separation or divorce, minority status, and male sex might undermine the prototype‐like stability of adolescent attachment. Stability of attachment was lower in adolescence relative to adulthood.